PEDAGOGICAL CONDITIONS AND STRUCTURAL AND FUNCTIONAL MODEL OF THE FORMATION OF HEALTH-PRESERVING COMPETENCE OF FUTURE PRIMARY SCHOOL TEACHERS (Physical Culture and Sport: Scientific Perspective, 2023)
The article examines pedagogical conditions and structural and functional model of the formation of health-preserving competence of future primary school teachers. We define the pedagogical conditions for the formation of the health-preserving competence of future primary school teachers as a complex of interconnected and purposefully created circumstances for the professional training of future teachers, the implementation of which ensures the effective application of the developed model of the studied process and the achievement of the expected result - positive dynamics of the levels of the formation of health-preserving competence of future primary school teachers.On the basis of the analysis of the works of many researchers and scientific approaches in this field, considering our own pedagogical experience, we have determined the following pedagogical conditions:• ensuring positive motivation of students to the formation of their health-preserving competence (value and motivational component);• organization of the educational process of a pedagogical institution of higher education on the principles of health-preserving personally oriented pedagogy, integration of educational courses and introduction of empirical learning systems (cognitive component);• activation of the use of interactive teaching methods in the process of professional training of future primary school teachers aimed at the formation of their health-preserving competence (operational and technological component and the component of personal and professional qualities of a teacher).Conducting professional training of future primary school teachers in pedagogical institutions of higher education, it was necessary to identify a required list of skills and knowledge of a teacher regarding the use of health-preserving competence in professional activities and to develop all components of structural and functional model of the formation of a future primary school teachers' health-preserving competence.In the process of the development of structural and functional model for the formation of health-preserving competence of future primary school teachers, general pedagogical and health-preserving principles, that define and specify the goal, were laid as its basis.
Keywords: health-preserving competence; health-preserving technologies; future primary school teachers; pedagogical conditions; structural and functional model